Organic coating on biochar explains its nutrient retention and stimulation of soil fertility. Issue 1 (December 2017) - Hagemann, Nikolas; Joseph, Stephen; Schmidt, Hans-Peter; Kammann, Claudia; Harter, Johannes; Borch, Thomas; Young, Robert; Varga, Krisztina; Taherymoosavi, Sarasadat; Elliott, K.; McKenna, Amy; Albu, Mihaela; et al.
Abstract Amending soil with biochar (pyrolized biomass) is suggested as a globally applicable approach to address climate change and soil degradation by carbon sequestration, reducing soil-borne greenhouse-gas emissions and increasing soil nutrient retention. Biochar was shown to promote plant growth, especially when combined with nutrient-rich organic matter, e.g., co-composted biochar. Plant growth promotion was explained by slow release of nutrients, although a mechanistic understanding of nutrient storage in biochar is missing. Here we identify a complex, nutrient-rich organic coating on co-composted biochar that covers the outer and inner (pore) surfaces of biochar particles using high-resolution spectro(micro)scopy and mass spectrometry. Fast field cycling nuclear magnetic resonance, electrochemical analysis and gas adsorption demonstrated that this coating adds hydrophilicity, redox-active moieties, and additional mesoporosity, which strengthens biochar-water interactions and thus enhances nutrient retention. This implies that the functioning of biochar in soil is determined by the formation of an organic coating, rather than biochar surface oxidation, as previously suggested. Biochar promotes plant growth via a slow release of nutrients; however, a mechanistic understanding of nutrient storage in biochar is lacking. Here, using high-resolution spectromicroscopy and mass spectrometry, the authors identify an organic coating on co-composted particles that enhances nutrient retention.